Influence of Unemployment Benefit on Duration of Registered Unemployment Spells - Beata Bieszk-Stolorz; Iwona Markowicz (Institute of Economic Research (IER), 2014)
The purpose of the article is to present the analysis of the influence of the unemployment benefit on the duration of the registered unemployment spells. The authors made a hypothesis that the very fact of receiving the benefit prolongs the job seeking time and determines the intensity of unemployment leaving. The power of this influence varies depending on a subgroup the unemployed person belongs to. The study was conducted on the basis of data from the Poviat Labour Office in Sulecin. The data were collected in the course of the European Union project implementation. The analysis covered two periods of time - before and after Poland's accession to the European Union and the change in legal regulations concerning unemployment benefits. In each of the periods the authors observed separate cohorts of the unemployed registered in 2001 and 2005. The closing dates of the observations were: the end of 2003 and 2007, respectively. Also, the authors examined whether the EU projects implemented after 2004 had an effect on the length of the unemployment spells as well as on the intensity of finding a job. The study confirmed the research hypotheses. The fact of claiming the unemployment benefit prolonged the unemployment spells in both periods of observation. The loss of the right to the benefit increased the probability of de-registration in each sub-group.
Keywords: C01; C14; J64; J65; A11; A14; B16; 330; Kaplan-Meier estimator; Cox hazard model; hazard ratio; unemployment